Steve: The Optical Signature of Intense Subauroral Ion Drifts. Issue 12 (26th June 2019) - Archer, W. E.; Gallardo‐Lacourt, B.; Perry, G. W.; St.‐Maurice, J. P.; Buchert, S. C.; Donovan, E.
Abstract: Little is currently known about the optical phenomenon known as Steve. The first scientific publication on the subject suggests that Steve is associated with an intense subauroral ion drift (SAID). However, additional inquiry is warranted as this suggested relationship as it is based on a single case study. Here we present eight occurrences of Steve with coincident or near‐coincident measurements from the European Space Agency's Swarm satellites and show that Steve is consistently associated with SAID. When satellite observations coincident with Steve are compared to that of typical SAID, we find the SAID associated with Steve to have above average peak ion velocities and electron temperatures, as well as extremely low plasma densities. Key Points: Eight Steve events were identified in all‐sky imager measurements with coincident or near‐coincident measurements from the Swarm satellites In all cases, evidence of subauroral ion drifts are observed in Swarm measurements All measurements of SAID overlapping with Steve have very fast ion flows, high electron temperatures, and extremely low plasma densities